A damper of torsional vibrations and an investigation of its efficiency - Spruogis, Bronislovas (Strojniški vestnik, 2006)
This paper reviews an original torsional vibration damper retaining its efficiency over a wide disturbing frequency band. Some potential design alternatives are considered. The basic structural element of the damper is a rotary flexible ring. The paper investigates the motion system on the basis ofa set of nonlinear differential equations. By separating the motion into uniform rotary and oscillatory, expanding the equation coefficients into a Taylor's power series and excluding the static members, a system of equations for insignificant oscillations is derived. The system contains inertia, flexible and gyroscopic terms. The equations of motion are derived and the stability conditions for the system's dynamic balance are formulated. Proper consideration is given to other possible loss-of-stability forms and regions of the flexible ring. An analysis of the system's natural frequencies is made.The efficiency estimation of the damper versus various parameters is effected as a result of the expression of the equivalent inertia moment and its limit values.
Keywords: dušilniki; vibracije; gibalne enačbe